Implementasi Pendidikan Ekologi Berbasis Sekolah Lapangan di SMK Bakti Karya Parigi - Siti Julaeha; Rina Marliani; Aini Ali Agustini; Samsudin Samsudin (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2023)
A lot of empty land that is left without any plants planted, can be an ideal place for the growth of weeds. At SMK Bakti Karya Parigi, vacant land is used as an object of field school-based ecological learning. The background of this research is to create innovation in conducting field schools. Field school-based Ecology Education is one of the learning methods at Bakti Karya Parigi Vocational School which aimsto provide a more practical and hands-on learning experience in the workplace. In this research, we aim to evaluate the implementation of Field School-Based Ecological Education at SMK Bakti Karya Parigi. This research method uses a qualitative approach that focuses on in-depth observation. Therefore, the use of qualitative methods in research can produce a more comprehensive study of a phenomenon. This research is intended to find out how to implement ecological understanding by conducting field schools. This research resulted in the implementation of field school-based management of ecological learning management that uses management functions in it